Short-course oral steroids as an adjunct therapy for chronic rhinosinusitis - Burton, M; Head, K; Chong, L; Hopkins, C; Philpott, C; Schilder, A (Cochrane Collaboration, 2015)
We reviewed the evidence for the benefits and harms of adding a short course (typically up to 14 days) of corticosteroid given by mouth to people with chronic rhinosinusitis who were also receiving another type of treatment (such as corticosteroids delivered through the nose). Background: Chronic rhinosinusitis is a common condition that is defined as inflammation of the nose and paranasal sinuses (a group of air-filled spaces behind the nose, eyes and cheeks). Patients with chronic rhinosinusitis experience at least two or more of the following symptoms for at least 12 weeks: blocked nose, discharge from their nose or runny nose, pain or pressure in their face and/or a reduced sense of smell (hyposmia). Some people will also have nasal polyps, which are grape-like swellings of the normal nasal lining inside the nasal passage and sinuses. Short courses of oral corticosteroids are a widely used treatment for chronic rhinosinusitis. They work by controlling inflammation and when polyps are present they rapidly reduce the size of the polyps to improve symptoms. The adverse effects of corticosteroids can include insomnia, mood changes and gastrointestinal changes (such as stomach pain, Short-course oral steroids as an adjunct therapy for chronic rhinosinusitis 3 / 45 heartburn, diarrhoea, constipation, nausea and vomiting). When given over the longer term, or through many repeated short courses, it is also possible to develop osteoporosis (fragile bones). Study characteristics: This review includes evidence up to 11 August 2015. We included two randomised controlled trials with a total of 78 participants. One trial involved 30 adults with nasal polyps. Participants received either intranasal corticosteroids and oral corticosteroids or only intranasal corticosteroids. The only result reported of interest to this review was whether the size of the nasal polyps was reduced, when these treatments were completed (three weeks). One trial involved 48 children (mean age of eight years) with chronic rhinosinusitis but no nasal polyps. Participants received either antibiotics and oral corticosteroids or only antibiotics and a placebo (sugar pill). The oral corticosteroids and placebo were given for 15 days and the antibiotics were given for 30 days. The trial reported findings when the antibiotic treatment was completed (at one month). Key results: At the end of a three-week treatment course, people who took both intranasal corticosteroids and oral steroids may have had smaller nasal polyps than people who just received intranasal corticosteroids. The trial did not follow up people to determine whether the polyp size increased after the end of the trial. The trial did not provide information on adverse events or other outcomes important to patients, such as symptom severity or quality of life. Children who received both antibiotics and oral corticosteroids seemed to have a lower total symptom score and better computerised tomography (CT) scan score after treatment compared with children who received antibiotics and control treatment. The reporting of adverse effects in this trial was not very clear and so is difficult to tell if any participant experienced gastrointestinal disturbances, mood changes or difficulty in sleeping. Quality of the evidence: We judged the quality of the evidence for oral steroids plus intranasal steroids for adults with nasal polyps to be very low (we are very uncertain about the estimate) as the evidence comes from one trial that has a low number of participants. The trial had a high risk of bias due to the way it was conducted. The trial did not report adverse events and did not report results after the end of treatment. We judged the quality of the evidence for oral steroids plus antibiotics for children to be low (further research is very likely to have an important impact on our confidence in the effect estimate and is likely to change the estimate) as the evidence comes from one small trial. The trial did not have a high risk of bias, but it only included children without nasal polyps, who might not have the same results as adults with nasal polyps. The trial did not report results after the end of treatment and the adverse effects of treatment were not well reported.